Work safety scale influcing safety behaviour in signaller army - Mohamad Syahir, Mohd Yusof (2025)
This study investigates the factors influencing safety behaviour in the Signaller Army, focusing on Work Safety Scale (WSS) factors, including co-worker safety, supervisor safety, management safety practices, and satisfaction of safety programs. The primary objectives were to assess the level of safety behaviour, analyse how WSS factors influence safety behaviour, and identify which WSS factors has the strongest impact on safety behaviour. A quantitative survey was conducted, collecting data from 295 military personnel, including Officers and Other Ranks. The data was analyzed using SPSS version 28.0, employing descriptive statistics, Pearson product-moment correlation coefficient analysis, and multiple regression analysis. The results revealed that Signaller Army personnel exhibited a high level of safety behaviour, with a mean score of 3.893. All WSS factors showed a significant positive relationship with safety behaviour. Specifically, co-worker safety (r = 0.552, p-value < 0.001), supervisor safety (r = 0.931, p-value < 0.001), management safety practice (r = 0.923, p-value < 0.001), and satisfaction of safety programs (r = 0.779, p-value < 0.001) were positively correlated with safety behaviour. Multiple regression analysis revealed that supervisor safety (b = 0.456) was the most influential factor, followed by management safety practices (b = 0.410), co-worker safety (b = 0.118), and satisfaction of safety programs (b = 0.091). These findings emphasize the importance of leadership, effective organizational practices, and strong teamwork in promoting safety behaviour within the military. The study offers valuable insights into improving safety culture and behaviour in military contexts, highlighting the need for targeted strategies to enhance safety culture and reduce operational risks